SISTEM PAKAR MENDIAGNOSA PENYAKIT THYPUS DI RUMAH SAKIT ROYAL PRIMA KOTA JAMBI - Surya, Junaidi; Desi Saputri, Mitya (LP2M Universitas Nurdin Hamzah, 2020)
Thypus is a disease that attacks the digestive tract and is caused by salmonella typhibacteria.Thypus disease is caused by rickettsia bacteria which spread through mice or other gnawig animals. These bacteria are usually found in foods and drinks contaminated with salmonella bacteria.for example, food that is not clean, files and many others. This research aim to produce a web-basd expert system application that is used to make a diagnosis of the type thypus disease based on symptoms experienced by the patient. During research the writer collects the data by using observation and interview method with party associated with this research in this case is a Neurologist. This website system developed with PHP programming language and MySQL database. The buit system will display the diagnostic result along with percentage of the calculation results with dempstershafermethod and will be equipped with suggestions aimed at the patients.